Implementation of the Government’s Internal Control System to Realizing Good Governance in Dinas Bina Marga dan Cipta Karya in Indonesia - Salma Nailurrohmah; Rudi Handoyono; Arum Febriyanti Ciptaningtias; Agni Astungkara (Vocational School, Universitas Sebelas Maret (UNS), Indonesia, 2024)
This study aims to analyze the implementation of the government's internal control system and its contribution to realizing good governance in Dinas Bina Marga dan Cipta Karya in one of the provinces in Indonesia. This study is mixed method research that used qualitative and quantitative method. In the qualitative method, the researchers used interviews, observation, and documentation. Two participants were staff of the office and were interviewed by the researchers. A total of 20 respondents were asked to fill out questionnaires. The results show that the implementation of the government's internal control system in Dinas Bina Marga dan Cipta Karya is excellent. However, a few shortcomings need to be addressed. Additionally, the contribution of the government's internal control system to good governance is significantly positive, accounting for 73.2%.